A preliminary study on the selection of self-heating elements in self-heating pads for instant tuna packaging / Nur Syukriah Ab Rahman … [et al.] - Ab Rahman, Nur Syukriah; Mohd Razali, Nur Ellyliana; Tuan Zainal Abidin, Tuan Muhammad Sadiq Zafran; Abd Rahman, Nur Syazwani; Mohamed Tap, Fatahiya; Derahman, Aishah; Mustafa, Iswaibah (Faculty of Applied Sciences, 2023)
Tuna is one of the travelers' most popular instant foods due to its delicious and nutritious taste. The innovation in food technology has offered a better experience for travelers in enjoying their meals by providing a self-heating pad to reheat the instant food. However, the commercial instant tuna available in the market nowadays offers no option for reheating purposes. Therefore, this study aimed to determine the best combination of materials to be developed as a self-heating pad for reheating that instant tuna. The most suitable characteristic of the combination of materials to be incorporated in a self-heating pad is the highest final temperature, the longest duration sustained at the highest temperature, and the shorter duration to achieve the highest temperature. In this current study, there are four (4) combinations of self-heating elements were evaluated, which are calcium oxide, sodium bicarbonate, and fe(iron); calcium oxide and zinc; calcium oxide and fe(iron); calcium oxide, sodium bicarbonate, and zinc. The reaction for each combination was activated with 100 mL and 200 mL of tap water, and the temperature of each reaction was recorded. Based on the theoretical calculation, 50.72℃ is the temperature needed to reheat the tuna with 100 ml of water, and 61.30 ℃ is the temperature needed to reheat the tuna with 200 ml of water. The result of this study indicated that the combination of 40 grams of calcium oxide and 6 grams of zinc in 100 ml water exhibited the highest temperature (76 ℃) with the time sustained at the highest temperature is 2 minutes and 13 seconds, and it took about 9 minutes and 20 seconds to achieve the highest temperature. Our study showed a promising finding where the highest temperature obtained by this combination exhibited higher temperature than the theoretically calculated temperature (50.72℃) needed to reheat the tuna. Therefore, considering the overall characteristic, 40 g of Calcium oxide and 6 grams of zinc along with 100 mL was chosen as the best material to be developed further as a self-heating element for reheating instant tuna.